Regulation of the Peptidoglycan Polymerase Activity of PBP1b by Antagonist Actions of the Core Divisome Proteins FtsBLQ and FtsN - Adrien Boes (American Society for Microbiology, 2019)
ABSTRACT Peptidoglycan (PG) is an essential constituent of the bacterial cell wall. During cell division, PG synthesis localizes at midcell under the control of a multiprotein complex, the divisome, allowing the safe formation of two new cell poles and separation of daughter cells. Genetic studies in Escherichia coli pointed out that FtsBLQ and FtsN participate in the regulation of septal PG (sPG) synthesis; however, the underlying molecular mechanisms remained largely unknown. Here we show that FtsBLQ subcomplex directly interacts with the PG synthase PBP1b and with the subcomplex FtsW-PBP3, mainly via FtsW. Strikingly, we discovered that FtsBLQ inhibits the glycosyltransferase activity of PBP1b and that this inhibition was antagonized by the PBP1b activators FtsN and LpoB. The same results were obtained in the presence of FtsW-PBP3. Moreover, using a simple thioester substrate (S2d), we showed that FtsBLQ also inhibits the transpeptidase domain of PBP3 but not of PBP1b. As the glycosyltransferase and transpeptidase activities of PBP1b are coupled and PBP3 activity requires nascent PG substrate, the results suggest that PBP1b inhibition by FtsBLQ will block sPG synthesis by these enzymes, thus maintaining cell division as repressed until the maturation of the divisome is signaled by the accumulation of FtsN, which triggers sPG synthesis and the initiation of cell constriction. These results confirm that PBP1b plays an important role in E. coli cell division and shed light on the specific role of FtsN, which seems to counterbalance the inhibitory effect of FtsBLQ to restore PBP1b activity. IMPORTANCE Bacterial cell division is governed by a multiprotein complex called divisome, which facilitates a precise cell wall synthesis at midcell and daughter cell separation. Protein-protein interactions and activity studies using different combinations of the septum synthesis core of the divisome revealed that the glycosyltransferase activity of PBP1b is repressed by FtsBLQ and that the presence of FtsN or LpoB suppresses this inhibition. Moreover, FtsBLQ also inhibits the PBP3 activity on a thioester substrate. These results provide enzymatic evidence of the regulation of the peptidoglycan synthase PBP1b and PBP3 within the divisome. The results confirm that PBP1b plays an important role in E. coli cell division and shed light on the specific role of FtsN, which functions to relieve the repression on PBP1b by FtsBLQ and to initiate septal peptidoglycan synthesis.